A pressure-jump study on the interaction of osmolytes and crowders with cubic monoolein structures. Issue 5 (11th January 2022) - Surmeier, Göran; Paulus, Michael; Schneider, Eric; Dogan, Susanne; Tolan, Metin; Nase, Julia
Abstract : Cellular solutes affect the equilibration of cubic lipid structures after pressure-induced phase transitions. Abstract : Many vital processes that take place in biological cells involve remodeling of lipid membranes. These processes take place in a milieu that is packed with various solutes, ranging from ions and small organic osmolytes to proteins and other macromolecules, occupying about 30% of the available volume. In this work, we investigated how molecular crowding, simulated with the polymer polyethylene glycol (PEG), and the osmolytes urea and trimethylamine- N -oxide (TMAO) affect the equilibration of cubic monoolein structures after a phase transition from a lamellar state induced by an abrupt pressure reduction. In absence of additives, swollen cubic crystallites form after the transition, releasing excess water over several hours. This process is reflected in a decreasing lattice constant and was monitored with small angle X-ray scattering. We found that the osmotic pressure exerted by PEG and TMAO, which are displaced from narrow inter-bilayer spaces, accelerates the equilibration. When the radius of gyration of the added PEG was smaller than the radius of the water channels of the cubic phase, the effect became more pronounced with increasing molecular weight of the polymers. As the release of hydration water from the cubic structures is accompanied by an increasing membrane curvature and a reduction of the interface between lipids and aqueous phase, urea, which has a slight affinity to reside near membrane surfaces, stabilized the swollen crystallites and slowed down the equilibration dynamics. Our results support the view that cellular solutes are important contributors to dynamic membrane processes, as they can accelerate dehydration of inter-bilayer spaces and promote or counteract membrane curvature.